Retailer replenishment policies with one-way consumer-based substitutionto increase profit and reduce food waste - Marjolein Elize Buisman; Rene Haijema; Eligius M. T. Hendrix (Logistics Research, 2020)
Retailers can exploit the consumer willingness to substitute to improve their profit, service level and waste. This paper investigates to what extent such improvement can be realised by the replenishment decisions. Two order policies are compared: one policy neglecting product substitution, and a new policy that decides on order quantities for all products simultaneously meanwhile anticipating stock-outbased substitution. Both policies are analysed by simulation-based optimization. Besides finding the optimal parameter values or a variety of settings by exact enumeration (as a benchmark), we present for the case of one-way substitution a heuristic search procedure. The heuristic finds (nearly) optimal parameter values quickly and turns out to find optimal parameter values in almost all settings. An average profit increase of almost 9% is obtained when anticipating on substitution, while waste levels can decrease with more than 35%. A clear trade-off between service levels and profit/waste levels is found. Assuming the retailer aims at profit maximization, the service level of one product maybe very low or even zero. The results provide the following managerial insights in: (i) the service levels and waste levels that maximize the retailer's profit, (ii) whether a product should be removed from the assortment, (iii) the profit loss and waste increase of setting a higher (sub optimal) service level, e.g. for strategic reasons. Reversely, one may learn from the results what the profit margin of a product should be to justify a certain service level to a profit maximizing retailer. These insights maybe useful to retailers whose primary objective is beyond profit maximization.
Keywords: 650; Retail; Food waste reduction; Substitution; Perishable; Multi-product